The Geography of accessibility: assessing the Malaysian approach to COVID-19 pandemic management - Fauziah Che Leh (Tanjong Malim, 2020)
The Geography of accessibility: assessing the Malaysian approach to COVID-19 pandemic management by Fauziah Che Leh